Modern RF and microwave measurement techniques - Teppati, Valeria, 1974- (New York : Cambridge University Press, 2013)
"This comprehensive, hands-on review of the most up-to-date techniques in RF and microwave measurement combines microwave circuit theory and metrology, in-depth analysis of advanced modern instrumentation, methods and systems, and practical advice for professional RF and microwave engineers and researchers. Topics covered include microwave instrumentation, such as network analysers, real-time spectrum analysis, sampling oscilloscopes and microwave synthesizers; linear measurements, such as VNA calibrations, noise figure measurements, time domain reflectometry and dielectric measurements; and non-linear measurements, such as load- and source-pull techniques, broadband signal measurements, and non-linear NVAs. Each technique is discussed in detail, and accompanied by state-of-the-art solutions to the unique technical challenges associated with its deployment. With each chapter delivered by internationally recognised experts in the field, this is an invaluable resource for researchers and professionals involved with microwave measurements"--
Part I. General Concepts: 1. Transmission lines and scattering parameters Roger Pollard and Mohamed Sayed; 2. Microwave interconnections, probing, and fixturing Leonard Hayden; Part II. Microwave Instrumentation: 3. Microwave synthesizers Alexander Chenakin; 4. Real-time spectrum analysis and time-correlated measurements applied to non-linear system characterization Marcus Da Silva; 5. Vector network analyzers Mohamed Sayed and Jon Martens; 6. Microwave power measurements Ronald Ginley; 7. Modular systems for RF and microwave measurements Jin Bains; Part III. Linear Measurements: 8. Two-port network analyzer calibration Andrea Ferrero; 9. Multiport and differential S-parameter measurements Valeria Teppati and Andrea Ferrero; 10. Noise figure characterization Nerea Otegi, Juan-Mari Collantes and Mohamed Sayed; 11. TDR based S-parameters Peter J. Pupalaikis and Kaviyesh Doshi; Part IV. Non-Linear Measurements: 12. Vector network analysis for nonlinear systems Yves Rolain, Gerd Vandersteen and Maarten Schoukens; 13. Load and source-pull techniques Valeria Teppati, Andrea Ferrero and Gian Luigi Madonna; 14. Broadband signal measurements for linearity optimization Marco Spirito and Mauro Marchetti; 15. Pulse and RF measurement Anthony Parker.
engineering bookfair2015
Includes bibliographical references and index.
Keywords: Radio measurements; Microwave measurements; Radio circuits; TECHNOLOGY & ENGINEERING / Microwaves